Recent and future environmental suitability to dengue fever in Brazil using species distribution model - Cardoso-Leite, Ricardo; Vilarinho, Ana Carolina; Novaes, Marcos Carneiro; Tonetto, Aurelio Fajar [UNESP]; Vilardi, Gabriel Cestari; Guillermo-Ferreira, Rhainer [UNESP] (Oxford University Press, 2014)
Background: Dengue fever is a mosquito-borne disease that affects more than 2.5 billion people worldwide. Here, we used the dataset of municipality infestation level from the Brazilian Health Ministry with the aim of building vector distribution models to identify epidemiological hotspots.Methods: Maxent software was used to predict the environmental suitability of the vector under current and 2050 climatic conditions. We built potential risk maps for current and future epidemiological scenarios in order to provide data for vector control planning.Results: The results showed that the current epidemiological status is critical in the coastal region, with 80% of the population in risk areas and 30% in epidemiological outbreak areas. Our results also suggest that the area covered by the vector distribution in Brazil will decrease in future projections in the north, but will spread to the south.Conclusions: The results may provide useful information for health agencies and policymakers in focusing efforts in epidemiological hotspots. Therefore, understanding the niche distribution dynamics of Aedes aegypti is an important step towards public health planning for vector control.
Keywords: Brazil; Culicidae; Dengue; Diptera; Epidemics; Insect vectors